The effect of aerodynamic characteristics on the drafting effect in track cycling - Heimans, L.; Dijkshoorn, W. R. (Journal of Science and Cycling, 2015)
Introduction: Since the aim of the men`s team pursuit is to accomplish a distance of 4000m as fast as possible, reducing aerodynamic drag by means of drafting can attribute in achieving this goal. Broker et al.1 quantified the average effect of drafting on power requirements in a team pursuit based on practical experimental data. However, since team members are not identical and will differ in aerodynamic characteristics, expressed as frontal projected areas (Ap) and drag coefficients (Cd), the reduction in power is likely to vary among individuals. A prediction of the magnitude of the drafting effect based on aerodynamic characteristics of team members can result in a more specific estimation for required power per position than the model of Broker et al.1 This study focuses on the effect of frontal area of team members on drag reduction, expressed as percentage of the drag coefficient measured in first position (drag fraction).